Panorama '85 is Definitely On - Unknown (Daily Express)
Panorama 1985 is on as it took two meetings between Pan Trinbago and the Minister of Sport, Culture and Youth Affairs to reach an agreement on the payment of salaries to officers who had taken no pay leave to organise Panorama. However, there would be no increase in prize money this year. The steelbands positions in the North/East preliminaries, the South preliminaries and pan-round-the-neck preliminaries are mentioned.
Keywords: Steel bands (Music) -- Administration -- Trinidad and Tobago; Steel bands (Music) -- Competitions -- Trinidad and Tobago; Panorama (Musical festival); Steel bands (Music) -- Trinidad and Tobago -- Finance